2017
DOI: 10.1038/nn.4479
|View full text |Cite
|
Sign up to set email alerts
|

REM sleep selectively prunes and maintains new synapses in development and learning

Abstract: The functions and underlying mechanisms of rapid eye movement (REM) sleep remain unclear. Here we show that REM sleep prunes newly-formed postsynaptic dendritic spines of layer 5 pyramidal neurons in the mouse motor cortex during development and motor learning. This REM sleep-dependent elimination of new spines facilitates subsequent spine formation in development and when a new motor task is learned, indicating a role of REM sleep in pruning to balance the number of new spines formed over time. In addition, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
378
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 437 publications
(406 citation statements)
references
References 57 publications
22
378
0
6
Order By: Relevance
“…Importantly, a recent study using adult mice trained on a motor task provided direct evidence that active sleep strengthens and maintains newly formed dendritic spines in primary motor cortex [65]; in three-week-old mice, which are undergoing rapid spine formation, active sleep exerted similar effects in motor cortex. Such studies, however, have not yet considered the possibility that twitching contributes to neural plasticity.…”
Section: Figurementioning
confidence: 99%
“…Importantly, a recent study using adult mice trained on a motor task provided direct evidence that active sleep strengthens and maintains newly formed dendritic spines in primary motor cortex [65]; in three-week-old mice, which are undergoing rapid spine formation, active sleep exerted similar effects in motor cortex. Such studies, however, have not yet considered the possibility that twitching contributes to neural plasticity.…”
Section: Figurementioning
confidence: 99%
“…Li and colleagues [77] showed that REM sleep appears to selectively prune and maintain new synapses associated with particular types of motor learning (Figure 2). Specifically, they found that REM sleep prunes newly formed postsynaptic dendritic spines on pyramidal neurons in the motor cortex after a new motor task is learned, and that REM sleep also strengthens and maintains these newly formed spines.…”
Section: Rem Sleep Functionmentioning
confidence: 99%
“…Given the role of active sleep in brain development, early active‐sleep disruption, or deprivation can be one such perturbation. Consistent with this idea, sleep deprivation affects synaptic plasticity in such sensorimotor structures as motor cortex, hippocampus, and cerebellum . In addition, because sensory feedback from twitching is a major source of stimulation to the neonatal brain, active sleep restriction, or deprivation can be also conceptualized as a form of sensory deprivation during critical periods for brain development.…”
Section: Causal Role Of Active‐sleep Disruption In Atypical Developmentmentioning
confidence: 98%